Evolution of Hemostasis Methods in Damage Parenchymatous Organs (Literature Review) (Eurasian Medical Research Periodical, 2023)
The article presents historical facts on the improvement of hemostasis over the past 100 years. A review of the classifications of liver and spleen injuries with prognosis and options for surgical interventions was carried out. The authors identified the range of unresolved problems, the existing positive and negative aspects of physical and chemical methods of local hemostasis, outlined ways to improve surgical methods for stopping parenchymal bleeding.